Potential therapeutic application of mesenchymal stem cells in COVID-19 complications - Emanuel Kolanko; Adam Mazurski; Piotr Czekaj (Nofer Institute of Occupational Medicine, 2021)
Mesenchymal stem cells (MSCs) have remarkable immunomodulatory properties, low immunogenicity, and paracrine properties as well as the ability to differentiate into multiple cell lines. These properties make them potential candidates for clinical applications in the treatment of neurodegenerative, cardiovascular, and lung diseases, which may be occupational diseases. Preclinical studies using experimental animal models have demonstrated regenerative properties of MSCs in diseases such as silicosis and occupational asthma. Currently, treatment of the novel disease COVID-19 could be enhanced by using MSC therapies. This disease affects many professional groups with great intensity and its consequences might be considered as an occupational disease. It is a significant public health problem and a therapeutic challenge. Despite the development of vaccines against COVID-19, there is growing concern about the emergence of new mutations of the SARS-CoV-2 virus in addition to the known alpha, beta, gamma, and delta variants. There is still no effective COVID-19 treatment and the existing ones only play a supporting role. MSCs offer treatment possibilities as an alternative or complementary therapy. The clinical trials to date using MSCs in patients with COVID-19 give hope for the safe and effective use of this stem cell population. Med Pr. 2021;72(6):693-700